Disparities and trends of the incidence and mortality of female-specific cancers in the United States - Ze Zhang; Yunhai Li; Hongbo Huang; Tingting Wei; Ying Huang; Xiuquan Qu; Yijing Xu; Aijie Zhang; Jiaying Li; Zheng Gong; Zhiqi Hu; Fan Li (PLoS ONE, 2025)
Background Female-specific cancers (FSCs) impose substantial burdens on healthcare systems and economies worldwide. The significant impact of these cancers in the United States warrants further investigation. Objective This study aimed to analyze trends in incidence and mortality rates of six female-specific cancers (breast, cervical, uterine, ovarian, vaginal, and vulvar cancers) among diverse racial and ethnic groups in the United States, and to evaluate the attributable contributions of major risk factors to the cancer death burden as well as their temporal changes. Methods Incidence and mortality data were obtained from the SEER (22 registry) database, to examine cross-sectional and temporal trends by race/ethnicity. The burden of FSCs attributable to specific risk factors was estimated based on the Global Burden of Disease 2021 database. Results Between 2017 and 2021, Breast cancer incidence increased across all racial groups, most notably among non-Hispanic White (White) women, while mortality declined. Cervical cancer incidence decreased in most groups but remained stable among American Indians and Alaska Native (AIAN) women. Uterine cancer incidence increased across all racial groups, except for Whites. Incidence and mortality rates for ovarian and vaginal cancers remained stable or decreased, whereas vulvar cancer mortality was highest among White and AIAN women and lowest among non-Hispanic Asian Americans and Pacific Islander (AAPI) women. From 2000 to 2021, risk-attributable deaths decreased for breast, cervical, and ovarian cancers but increased for uterine cancer. Conclusions Significant sociodemographic disparities and unfavorable trends persist in the incidence and mortality of all six major female-specific cancers, highlighting the importance for effective prevention and intervention strategies.